Harnessing Momentum : Priority Areas of Intervention to Further Strengthen Malawi’s Health Sector - World Bank (World Bank, Washington, DC, 2021)
Malawians are healthier and live longer than they ever have. Achieving universal health coverage in a sustainable and equitable way is the main goal of Malawi’s health sector reform plan, and an essential health package (EHP) free at the point of use is the government’s primary tool to achieve this. Malnutrition also remains an ongoing challenge. Malawi’s Second Health Sector Strategic Plan (HSSP) for 2017-2022, identifies a set of interventions necessary to further improve health outcomes, and to ensure the delivery of quality, equitable, affordable and patient-centred health care services. Malawi’s 2018-2019 Harmonised Health Facility Assessment (HHFA), conducted by the government of Malawi with support from international health and development agencies, provides a comprehensive including government, faith-based, CHAM (Christian Health Association of Malawi) and private for-profit facilities between November 2018 and March 2019. This policy brief draws from this assessment, as well other research, identifying the most important policy interventions needed to achieve key health targets over the coming years.